Translanguaging as an Instructional Strategy in Adult ESL Classroom - Mehedi Hasan; A B M Shafiqul Islam; Israt Jahan Shuchi (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
The use of the first language (L1) in adult second (L2/SL) or foreign language (FL) classrooms has always been a bone of contention over the past few decades. Many are in favor of L1 use terming it as constructive and facilitating for language learning while some disapprove that practice and identify it as a hindrance to the teaching and learning of a language. Of late, the concept of translanguaging has added a new dimension to this long-standing debate of using L1 in teaching/learning L2 since it basically insists on viewing languages as a single unitary system as opposed to the traditional linguistic perception of L1 versus L2. However, there have only been a very few studies on translanguaging with particular emphasis and attention given to ESL/EFL adults at the college/university level. This research study thus attempts to shed light on the theoretical underpinnings of this L1-L2 dichotomy and discuss how translanguaging differs from the customary notion of using L1 in the adult L2 classroom. This study uses a qualitative research method that exclusively uses the relevant secondary references/works available on the topic. The results demonstrated that both translanguaging and the notion of L1use in the L2 classroom are pedagogically similar as both allow the use of L1 in L2 classrooms at varying degrees though theoretically, they are different.